2013
DOI: 10.1007/s00248-013-0273-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Brachyspira spp. Including “Brachyspira hampsonii” from Lesser Snow Geese (Chen caerulescens caerulescens) in the Canadian Arctic

Abstract: Brachyspira is associated with diarrhea and colitis in pigs, and control of these pathogens is complicated by their complex ecology. Identification of wildlife reservoirs of Brachyspira requires the discrimination of colonized animals and those simply contaminated through environmental exposure. Lesser snow geese (Chen caerulescens caerulescens) were sampled in the Canadian arctic during the summer of 2011, and cloacal swabs were cultured on selective media. Brachyspira isolates were obtained from 15/170 (8.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
4
32
0
Order By: Relevance
“…B. intermedia isolates are known to cause disease in chickens, and although they are frequently isolated from swine, they are not usually associated with disease in this host species (24). Similarly, although B. hampsonii has been isolated from birds (10,11), to our knowledge it is only known to cause disease in swine (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…B. intermedia isolates are known to cause disease in chickens, and although they are frequently isolated from swine, they are not usually associated with disease in this host species (24). Similarly, although B. hampsonii has been isolated from birds (10,11), to our knowledge it is only known to cause disease in swine (1).…”
Section: Discussionmentioning
confidence: 99%
“…The migratory patterns of wild birds, their close contact with livestock, and contamination of drinking water sources by their feces may allow the spread of and exposure of livestock to infectious agents, thus suggesting their potential role as reservoirs (34). Additionally, a previous study (11) reported colonization without clinical signs in an experimental inoculation of a B. hampsonii clade II (or genetic group II) isolate that was isolated from a migratory bird (snow goose). Therefore, the clustering of migratory wild bird-origin B. hampsonii isolates with those of swine origin in this study provides further support for the hypothesis of B. hampsonii transmission between these host species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence analysis at present is considered the gold standard for specieslevel identification Perez et al 2016). DNA sequencing has revealed phylogenetic diversity within the genus Brachyspira, including the novel strain "B. hampsonii" and a large number of other strains that have not yet been characterized but appear to be distinct from recognized species (Patterson et al 2013;Rubin et al 2013b). …”
Section: Taxonomymentioning
confidence: 99%